Izaak I Komnen (1007-1060). Wódz, buntownik, cesarz - w poszukiwaniu jego doktryny wojennej? - Böhm, Marcin (Vox Patrum, 2021)
Isaac Komnenos (1007–1060) was the first representative of his family to sit on the imperial throne in Constantinople. He was raised by Emperor Basil II (976–1025). During his unusually short reign heattempted to rectify the errors of his predecessors, who at the end of the Macedonian dynasty left the Empire militarily weak. This would not have been possible without military education supplemented by hands-on experience that Isaac acquired during his years of service at various levels in the Byzantine army. Is it possible, then, to outline the war doctrine that guided this man at various stages of his service, and whose end was the imperial purple? The coins and seals remaining after the reign of this basileus are clear evidence of attempts to rebuild the prestige propaganda of Byzantine weaponry and the majesty of imperial rule. Isaac referred to his great predecessor and protector Basil II, who in a style similar to that of Komnenos is depicted on coins with a menologium made for him. It also well reflects the military doctrine that Isaac Komnenos followed throughout his adult life. He was not in any way the creator of a new approach to the Byzantine military of that period, but rather he continued the work of Basil II, John I Tzimiskes and Nikephoros II Phokas. It was a difficult task in the geopolitical circumstances of Byzantium at the beginning of the second half of the 11th century, mainly because of nomads pressing against the imperial borders in Europe and Asia. Unfortunately, Isaac did not have enough time to complete it.